Rekontruksi Epistemologi Politik : Dari Humanistik Ke Profetik - Nur, Muhammad (UIN Sunan Kalijaga, 2014)
Politic, in every episode of history, seems full of intrict that pragmatics, so that politic the same with cruel, dirthy and anomaly. Many of stakeholders appriory by this situation. This is make politic more and more tiranic offcourse. That is way, very important think to advocate ethic and moral politic which base on universal values of prophet, namely prophetic of politic. Core of this models is humanis, liberation and transendental. The implementations of this model take in Islamic nomocration, as main of state management.